Konsep Diri dan Kondisi Psikologis sebagai Prediktor Kepuasan Seksual pada Pasien Tuberkulosis Paru - Naela Hidayati; Sukesih Sukesih; Sri Karyati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Pulmonary tuberculosis not only causes chronic physical impairment but also affects patients’ psychological well-being, self-concept, and the quality of their intimate relationships, which in turn impacts sexual satisfaction. This study aims to analyze the relationship between self-concept and psychological well-being as predictors of sexual satisfaction among patients with pulmonary tuberculosis at Prima Medika Hospital in Pemalang. The study employed a quantitative correlational approach with a cross-sectional design involving 53 respondents selected using purposive sampling. Data collection was conducted using questionnaires on self-concept, psychological condition, and sexual satisfaction, all of which had been validated for validity and reliability. Data analysis utilized the Spearman’s rank correlation test via SPSS version 26. The results indicated a significant negative correlation between self-concept and sexual satisfaction with a correlation coefficient of -0.467 (p < 0.01), as well as a significant positive correlation between psychological condition and sexual satisfaction with a correlation coefficient of 0.507 (p < 0.01). These findings indicate that psychological distress, social stigma, and changes in self-perception contribute to a decline in the quality of sexual life among patients with pulmonary tuberculosis. A biopsychosocial approach to healthcare is necessary to improve patients’ quality of life more comprehensively.